Visualizing nanoscale 3D compositional fluctuation of lithium in advanced lithium-ion battery cathodes - A. Devaraj (7221497) (2015)
The distribution of cations in Li-ion battery cathodes as a function of cycling is a pivotal characteristic of battery performance. The transition metal cation distribution has been shown to affect cathode performance; however, Li is notoriously challenging to characterize with typical imaging techniques. Here laser-assisted atom probe tomography (APT) is used to map the three-dimensional distribution of Li at a sub-nanometre spatial resolution and correlate it with the distribution of the transition metal cations (M) and the oxygen. As-fabricated layered Li1.2Ni0.2Mn0.6O2 is shown to have Li-rich Li2MO3 phase regions and Li-depleted Li(Ni0.5Mn0.5)O2 regions. Cycled material has an overall loss of Li in addition to Ni-, Mn- and Li-rich regions. Spinel LiNi0.5Mn1.5O4 is shown to have a uniform distribution of all cations. APT results were compared to energy dispersive spectroscopy mapping with a scanning transmission electron microscope to confirm the transition metal cation distribution. Other Information Published in: Nature Communications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/ncomms9014